A bibliometric analysis of halal tourism research: Indonesia and Malaysia - Misbah, Hanim; Johari, Fuadah (Faculty of Business & Economics, Universitas Islam Indonesia, 2024)
Purpose – Halal tourism has grown significantly, driven by the increasing global Muslim population and disposable income. However, comprehensive analysis of the research landscape is lacking. This study bridges this gap by conducting a bibliometric analysis of halal tourism research from 2014 to 2024 and examining growth trends, key contributors, and collaborative networks.Methodology – Using Scopus data, 244 documents from 132 sources were analyzed.Findings – Research on halal tourism has grown at an annual rate of 34.24%. Contributions from 645 authors, averaging 3.25 co-authors per document, indicate robust collaboration. Key journals include the Journal of Islamic Marketing, Journal of Environmental Management and Tourism, and Tourism Management Perspectives. Thematic clusters include economic impact, marketing strategies, sustainability, and religious aspects. Indonesia and Malaysia, led by Universitas Airlangga and the University of Malaya, dominate the research output and citation impact. The findings suggest that enhancing visibility and impact requires focusing on high-quality projects, strategic collaboration, and active dissemination.Implications – This study identifies key trends and research gaps, guiding future studies, and fostering interdisciplinary collaboration. For industry stakeholders, it underscores the importance of targeted marketing and sustainable practices in catering to Muslim travelers. Policymakers should be encouraged to develop standardized halal tourism frameworks, enhance international collaboration, and support research initiatives for sustainable sector growth.Originality – This study offers a unique perspective through a comparative bibliometric analysis of halal tourism research in Indonesia and Malaysia, identifying emerging trends and collaboration networks, while providing new directions for future studies and partnerships.